LEARNING ANALYSIS: IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN IMPROVING NUMERACY LITERACY IN ELEMENTARY SCHOOLS - Santi Hindriyanti Hindri; Astri Sutisnawati; Dyah Lyesmaya (Universitas Pendidikan Indonesia, 2023)
This research was conducted to find out and examine the implementation of the Independent Curriculum learning in increasing numeracy literacy at SDN Selaawi, Sukabumi Regency. This research was conducted using a descriptive qualitative method with a phenomenological approach. This approach was chosen because the problems studied concern issues that are currently developing in life, especially in the education unit curriculum. This research was conducted at Selaawi Elementary School, Sukabumi Regency, the subjects in this study were school principals, class I and IV teachers, and class I and IV students in the 2022/2023 academic year. Data collection was carried out using several techniques, namely: (1) observation; (2) interviews; and (3) documentation. The data analysis technique used is the data analysis technique of the model Miles Huberman which has three flow of activities, namely: (1) data reduction; (2) data presentation; and (3) drawing conclusions. Based on the results of the research, it shows that the implementation of the Independent Curriculum has a positive impact on the learning process, and there is an increase in students' numeracy literacy with programs that support this increase.